Bio-efficacy of some Insecticides against Chrysodeixis acuta Walk. and Obereopsis brevis Swed. Infesting Soybean - Chaudhary, H R; Meghwal, H P (Annals of Arid Zone, 2016)
Six insecticides i.e. Indoxacarb 14.5 SC @ 0.3 L ha-1, Indoxacarb 14.5 SC @ 0.15 L ha-1, Diafenthiuron 50 WP @ 0.5 kg ha-1, Profenophos 50 EC @ 1.25 L ha-1, Lamdacyhalothrin 5 EC @ 0.3 L ha-1, Emamectin benzoate 5 SG @ 0.18 kg ha-1 and Triazophos 40 EC @ 0.8 L ha-1 were evaluated for their efficacy against green semilooper Chrysodeixis acuta (Noctuidae: Lepidoptera) and girdle beetle Obereopsis brevis (Lamiidae: Coleoptera) at Agricultural Research Station, Ummedganj, Kota (Rajasthan), during kharif 2005 and 2006. The treatment of Indoxacarb 14.5 SC @ 0.3 L ha-1 was most effective against green semi-looper, where only 0.08 larvae m-1 row length was recorded after 5 days of treatments followed by Diafenthiuron 50 WP @ 0.5 kg ha-1 (0.12 larvae m-1 row length), Profenophos 50 EC @ 1.25 L ha-1 (0.12 larvae m-1 row length), Triazophos 40 EC 0.8 L ha-1 (0.16 larvae m-1 row length), Lamdacyhalothrin 5 EC 0.3 L ha-1 (0.20 larvae m-1 row length). The treatment of Triazophos 40 EC @ 0.8 L ha-1 was most effective against girdle beetle, where only 0.74% infestation was recorded after 5 days of treatment followed by Lamdacyhalothrin 5 EC 0.3 L ha-1 (1.87%), Diafenthiuron 50 WP @ 0.5 kg ha-1 (1.90%), Indoxacarb 14.5 SC @ 0.3 L ha-1 (2.24%). Maximum seed yield was found in the treatment of Triazophos 40 EC 0.8 L ha-1 (1980 kg ha-1) followed by Indoxacarb 14.5 SC 0.3 L ha-1 (1970 kg ha-1) but were statistically at par. The maximum net return (Rs 3606 ha-1) was found in the treatment of Triazophos 40 EC 0.8 L ha-1 followed by Indoxacarb 14.5 SC 0.3 L ha-1 (Rs 2646 ha-1) and Lamdacyhalothrin 5 EC 0.3 L ha-1 (Rs. 2541 ha-1). Key words: Green semi-looper, girdle beetle, soybean, insecticide.